Arthroscopic Lateral Ulnar Collateral Ligament Plication/Reconstruction With Augmented Lateral Collateral Ligament Imbrication - Christos Koukos, M.D.; Dominique Schoeps, M.D.; Joachim Windolf, M.D.; In-Ho Jeon, PhD, M.D.; Cristina Zolog, M.D.; Konstantinos Ditsios, PhD., M.D.; David Latz, M.D. (Arthroscopy Techniques, 2025)
Posterolateral rotatory instability (PLRI) is a chronic condition resulting from damage to the lateral ulnar collateral ligament (LUCL) and related structures causing painful restrictions and instability in elbow movement. Conservative treatment often falls short, necessitating surgical intervention to restore elbow stability. Traditionally, open LUCL reconstruction with tendon grafting has been the standard of care but involves substantial tissue disruption and extended recovery. Arthroscopic approaches offer a less-invasive alternative with reduced soft-tissue damage and faster recovery. This Technical Note presents an algorithm-driven, arthroscopically assisted technique for PLRI treatment. Using magnetic resonance imaging to evaluate the common extensor origin’s integrity, surgical options include LUCL plication with anchor fixation and lateral collateral ligament imbrication. During surgery, a minimally invasive technique is employed leveraging arthroscopy for precise ligament inspection and anchor-based fixation. Sutures stabilize the LUCL and lateral collateral ligament, addressing instability while preserving tissue integrity. This approach enables rapid postoperative rehabilitation and reduces the risk of motion restrictions. Although suitable for grade 1 and 2 PLRI, the technique demands high arthroscopic proficiency. This minimally invasive method allows effective management of elbow instability while promoting quicker patient recovery and long-term functional restoration.